PENGARUH REBUSAN DAUN SIRIH MERAH TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM DI WILAYAH KERJA UPTD PUSKESMAS TARAJU KABUPATEN TASIKMALAYA : The Effect Of Red Betel Leaf Brewing On The Healing Of Perineal Wounds In Postpartum Mothers In The Working Area Of The Taraju Community Health Center Uptd, Tasikmalaya Regency - Nia Kurniasih (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2025)
Background : One of the contributors to AKI in Indonesia is infection due to woundsperineum in postpartum mothers. The incidence of perineal wounds in the world is 2.7 million cases, in Indonesia 75%, in West Java 71%, in Tasikmalaya Regency 11.9% and in UPTD Taraju Health Center 6% and 1 case of morbidity due to perineal wound infection. One effort to speed up wound healingperineum namely by giving decoction of red betel leaves. Research purposes to determine the effect of giving boiled red betel leaves to postpartum mothers in the working area of the UPTD Taraju Health Center, Tasikmalaya Regency.Research method: Research design:quasy experiment with a planpre and posttest whit control group design. Population: all motherspostpartum with woundsperineum in the UPTD work area of the Taraju Community Health Center, Tasikmalaya Regency in January 2024. Sampling technique:acidental sampling based on inclusion and exclusion criteria. The total sample was 40 people, divided into 2 groups, namely an experimental group of 20 people who were treated with red betel leaf decoction and a control group of 20 people who were given a placebo decoction. The research instrument consists of a questionnaire sheet, monitoring sheet and observation sheet. Research location: UPTD work area of the Taraju Community Health Center, Tasikmalaya Regency, from June 2023 to March 2024. Data analysis: univariate and bivariate with tests Man whitney.Research Results: The mean rank of the experimental group (10.63) was ranked higher than the control group (30.38) from the overall ranking in order of the greatest value of perineal wound healing from ranks 1-40. Statistical test results withuji Man Whitney significant results were obtained withp value 0.000 then Ho is rejected and Ha is accepted.Conclusion: there is an effect of giving red betel leaf decoction on wound healing perineum on the mother postpartum in the UPTD work area of the Taraju Health Center, Tasikmalaya Regency